2008
DOI: 10.2298/jas0802091a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophytometeorological indexes of Virginia type tobacco

Abstract: The field trial of Virginia type tobacco (Hevesi-9) was set in irrigation conditions, in the vicinity of Brzi Brod village, Nišava River's valley, on the alluvium soil type. Water consumption for evapotranspiration, at the irrigated variant and the control one, was calculated for each month and the whole vegetation period, by making the balance between water consumption from the soil layer to 2m under the ground, total precipitation amount in the vegetation and water added by irrigation. Hydro-phyto-meteorolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There was a logarithmic relationship between evapotranspiration and the total tuber yield with a R 2 of 0.93 [y=31.385ln(x)-168.65] and between IW and the total tuber yield with a R 2 of 0.87 [y=15.313ln(x)-58.73] (Figure 4 and Figure 5). While Kızıloğlu et al (2006), Ayas and Korukçu (2010) and Cantore et al (2014) reported a linear relationship between evapotranspiration and tuber yield, Aksic et al (2014), stated that a quadratic relation between potato yield and crop evapotranspiration. Ross (2006) found a cubic polynomial relationship between potato yield and the seasonal IW amount and Karam et al (2014) determined a strong quadratic relationship between fresh potato tuber yield and seasonal IW in Agria cultivar.…”
Section: Water Yield Relationshipsmentioning
confidence: 99%
“…There was a logarithmic relationship between evapotranspiration and the total tuber yield with a R 2 of 0.93 [y=31.385ln(x)-168.65] and between IW and the total tuber yield with a R 2 of 0.87 [y=15.313ln(x)-58.73] (Figure 4 and Figure 5). While Kızıloğlu et al (2006), Ayas and Korukçu (2010) and Cantore et al (2014) reported a linear relationship between evapotranspiration and tuber yield, Aksic et al (2014), stated that a quadratic relation between potato yield and crop evapotranspiration. Ross (2006) found a cubic polynomial relationship between potato yield and the seasonal IW amount and Karam et al (2014) determined a strong quadratic relationship between fresh potato tuber yield and seasonal IW in Agria cultivar.…”
Section: Water Yield Relationshipsmentioning
confidence: 99%
“…The method is described in literature. (e.g., [81][82][83][84][85][86][87]). The bioclimatic method in the Vojvodina region was developed by [88] and it is based on the correlation between crop evapotranspiration and physical factors of evapotranspiration (temperature, humidity, solar radiation, vapor pressure, etc.).…”
Section: Phase Ii-thementioning
confidence: 99%
“…Albedo of potato fields was found to be 9-21%; for example, the values 13-25% (wheat) and 14-36% (barley) were reported in different publications (e.g., Tajchman 1971, Piggin andSchwerdtfeger 1973). Also, Aksic et al (2014) showed the effect of matric potential (or water consumption for evapotranspiration) on potato yields etc. (Kang et al 2004).…”
mentioning
confidence: 91%